Tarih Öğretiminde Öğrencilere Yönelik Yayımlanan Ticari Kitaplara İlişkin Yazar Görüşleri / The Opinions of Author Related to Trade Books Published for Students in History Teaching - Kale, Yeliz (Journal of History Culture and Art Research, 2018)
Abstract Students’ history reading and learning materials are not limited to school history textbooks. One of the tools of history learning is trade books. Trade books are one of the important materials that can influence the shaping of the students’ knowledge and consciousness of history. The purpose of this study is to determine the opinions of authors on published trade history books for students. This study was designed as a qualitative one. The participant group of the study consisted of six authors who write trade books for students. In this study, the criterion sampling method was used as one of the ways of purposeful sampling to specify the study group. The data were collected with a questionnaire consisting of open-ended questions. The data obtained were analyzed by using the descriptive analysis technique. According to the findings of the study, it was observed that the participants emphasized the use of scientific and reliable sources as the criteria they considered while writing a book. The participants think that books can help students to enrich their knowledge, make learning easier, contribute to reading, and increase interest in history. It was determined that the participants’ opinions about the difficulties they encountered in writing the books varied. Half of the participants stated that in history trade books, there are problems such as exaggerated expressions and interpretations, diversion from academic historicism, misinformation. In terms of the features that should be included in a qualified trade history book written for the students; it has been determined that books emphasize the importance of being unbiased, written, entertaining, intriguing, with the right information. Öz Öğrencilerin tarih okuma ve öğrenme materyalleri sadece okuldaki tarih ders kitapları ile sınırlı değildir. Tarih öğrenmenin araçlarından biri de ticari kitaplardır. Ticari kitaplar öğrencilerin tarih bilgisinin ve bilincinin şekillenmesine etki edebilecek önemli materyallerden biridir. Bu araştırmanın amacı, öğrencilere yönelik yayımlanan ticari tarih kitaplarına ilişkin yazarların görüşlerini belirlemektir. Çalışmada nitel araştırma yöntemi kullanılmıştır. Araştırmanın katılımcı grubunu öğrencilere yönelik ticari kitap yazan altı yazar oluşturmuştur. Katılımcıların belirlenmesinde amaçlı örnekleme yöntemlerinden, ölçüt örnekleme yöntemi kullanılmıştır. Araştırmada veriler, açık uçlu sorulardan oluşan bir anket ile toplanmış ve elde edilen veriler betimsel analiz tekniği ile çözümlenmiştir. Araştırmanın bulgularına göre, katılımcıların kitap yazarken dikkate aldıkları kriter olarak, bilimsel ve güvenilir kaynaklardan yararlanılması konusuna daha çok vurgu yaptıkları görülmüştür. Katılımcılar, kitapların öğrencilere; bilgilerini zenginleştirme, öğrenmeyi kolaylaştırma, okumaya katkıda bulunma, tarihe ilgiyi artırma konusunda yarar sağlayabileceğini düşünmektedir. Katılımcıların, kitapları yazarken karşılaştıkları zorluklar ile ilgili görüşlerinin ise çeşitlilik gösterdiği tespit edilmiştir. Katılımcıların yarısı ticari tarih kitaplarında; abartılı anlatım ve yorumların olması, akademik tarihçilikten uzaklaşılması, bilgi yanlışlarının olması gibi sorunların olduğunu ifade etmiştir. Öğrencilere yönelik yazılan nitelikli bir ticari tarih kitabında bulunması gereken özellikler konusunda; kitapların doğru bilgilerle tarafsız yazılması, eğlenceli, ilgi çekici, merak uyandırıcı olması gerektiğine ilişkin görüşün daha çok vurgulandığı tespit edilmiştir.